Coeliac disease. Issue 10344 (25th June 2022) - Catassi, Carlo; Verdu, Elena F; Bai, Julio Cesar; Lionetti, Elena
Summary: Coeliac disease is an autoimmune disorder that primarily affects the small intestine, and is caused by the ingestion of gluten in genetically susceptible individuals. Prevalence in the general population ranges from 0·5% to 2%, with an average of about 1%. The development of the coeliac enteropathy depends on a complex immune response to gluten proteins, including both adaptive and innate mechanisms. Clinical presentation of coeliac disease is highly variable and includes classical and non-classical gastrointestinal symptoms, extraintestinal manifestations, and subclinical cases. The disease is associated with a risk of complications, such as osteoporosis and intestinal lymphoma. Diagnosis of coeliac disease requires a positive serology (IgA anti-transglutaminase 2 and anti-endomysial antibodies) and villous atrophy on small-intestinal biopsy. Treatment involves a gluten-free diet; however, owing to the high psychosocial burden of such a diet, research into alternative pharmacological treatments is currently very active.